Effects of heat treatment on the atomic structure and surface energy of rutile and anatase TiO2 nanoparticles under vacuum and water environments. (2nd June 2016) - Okeke, George; Hammond, Robert Bryan; Antony, Simon Joseph
Abstract: Nanomaterials have become a widely used group of materials in many chemical engineering applications owing to their ability to provide an enhanced level of functional properties compared to their crystalline and bulk counterparts. Here we report fundamental level advancements on how the anatase and rutile phase of TiO2 nanoparticles chemo-thermally respond between room temperature and the melting temperature under both vacuum and water environments. The current study is based on using molecular dynamics (MD) simulations. We present results on the equilibrium crystal morphology of these phases, structural and surface energy of TiO2 nanoparticles in the size range of 2–6 nm under different temperatures. Thermodynamic and structural properties, in the form of potential energy and Radial Distribution Functions (RDF's) respectively, are calculated for both forms of TiO2 nanoparticles. The temperature associated with the melting transition increased with an increase in the particle size in both the phases. The potential energy change associated with the melting transition for anatase was seen to be less than that for rutile nanoparticles. Also the temperature at which the RDF's began to stretch and broaden was observed to be lower for the case of anatase than rutile, suggesting that rutile attains the most thermal stable phase for the nano particle sizes considered in this study. Structural changes in anatase and rutile nanoparticles under different temperatures revealed that non-spherical (rod-like) rutile nanoparticles tend to be thermodynamically more stable. Surface energy influences the shape of TiO2 nanoparticles at different temperatures. The increase in the surface energy of nanoparticles under vacuum when compared with that of water environment is higher for the anatase phase than the rutile phase of nanoparticle sizes studied here. The fundamental level simulation results reported here provide a strong platform for potentially accounting for the effects of atomic-scale phase characteristics of TiO2 nanoparticles and surface energy under different temperature fields in nano processing applications and related multi-scale modelling approaches in future. Graphical abstract: Highlights: Prediction of equilibrium crystal morphology for rutile and anatase TiO2 . Thermodynamic and structural properties of rutile and anatase are presented. Estimation of melting transition temperature for both phases of TiO2 . Non-spherical rutile nanoparticles tend to be thermodynamically more stable. Surface energy influences the shape of TiO2 nanoparticles at different temperatures.